Safety and effectiveness of office hysteroscopic metroplasty with and without uterine stent placement in infertile population: a 10-year retrospective study - Mitko Madjunkov; Jak Ozsarfati; Ari Baratz; Karen Glass; Prati Sharma; Clifford Librach (Therapeutic Advances in Reproductive Health)
Background: Septate uterus is a congenital uterine malformation associated with adverse reproductive and obstetrical outcomes. Hysteroscopic septum resection (HSC) with/without balloon stent placement is a treatment option for reconstituting to a normal uterine cavity; however, procedure safety and efficacy of office-based-ultrasound guided (US) HSC in patients undergoing fertility treatment is not thoroughly studied. Objectives: (1) To assess the safety and efficacy of office-based US-guided HSC septoplasty; (2) compare the safety and effectiveness of adjuvant intrauterine-balloon-Cook stent (IUBS) and (3) to evaluate the reproductive outcomes after each method. Design: Retrospective cohort study. Methods: We conducted a retrospective cohort study ( n  = 90) of patients undergoing HSC at the CReATe Fertility Centre, Toronto, Canada between 2011–2022. The Congenital Uterine Malformation by Experts (CUME-2018) guideline’s criteria were used for diagnosis and classification of malformation/septum size as 1—arcuate uterus <10 mm (52% (47/90)), 2—septum 10–19 mm (31% (28/90)), 3—septum 20–40 mm (7% (6/90)), and 4—complete septa (10% (9/90)). The main outcomes were the rate of procedure complications and the efficacy of septum removal. Secondary outcome measures were reproductive outcomes after septoplasty and the safety and effectiveness of adjuvant IUBS placement. T -test and chi-square test, McNemar test, and Cochran-Mantel–Haenszel test were used for stratified statistical analysis. Results: Office-HSC under US guidance was performed in 82 patients (US group) and septoplasty with laparoscopic guidance in 8 patients laparoscopy (LSC) group. IUBS placement had 34% (28/82) of patients in the US group and 12.5% (1/8) in the LSC group. There were no intraoperative or postoperative complications (uterine perforations, excessive bleeding, or infections) in either group. The rate of repeated procedures, implantation, pregnancy, and live birth rates (LBR) were not different when comparing septoplasty with and without IUBS. However, for patients diagnosed with septum class-2, -3, and -4, septoplasty improved their pre-treatment-LBR from 21.6% (8/37) to 77.1% (27/35) post-treatment ( p  = 0.00005) and decreased pre-treatment miscarriage rate (MR) from 73% (27/37) to post-treatment 29% (7/24) ( p  = 0.0007) in both groups. Conclusion: Hysteroscopic septum resection with transabdominal US guidance in the office setting is a safe and effective procedure in patients with infertility. Office hysteroscopy should be considered in the management of patients with uterine septum to improve LBR and reduce MR. The value of IUBS needs further evaluation in a larger sample-size study.